Performance Ranks, Conformity, and Cooperation: Evidence from a Sweater Factory - Anik Ashraf (Center for Economic Studies and ifo Institute (CESifo), 2022)
Performance ranks introduce a trade-off for workers. They have to choose between signaling high productivity or signaling social compatibility to peers. Using a long-term experiment at a sweater factory, this paper disentangles the incentives underlying performance ranks. Treated workers receive either private or public ranks. In response, intrinsic incentives from private ranks do not affect productivity. But publicly-ranked workers reduce productivity to conform to their social groups in the workplace. Additionally, cooperation decreases among the workers, although with limited effect on productivity. The paper shows how inducing competition among workers may be counterproductive for firms.
Keywords: D23; J53; O15; 330; ranks; social conformity; cooperation